Republic of Korea : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper for the Republic of Korea focuses on the role of monetary policy in the current context of slowing growth and rising inflation pressures. Korea has not remained immune to the global slowdown, and with the cycle turning downward, the trade-off between inflation and growth is deteriorating. Subprime-related turbulences in financial markets add an extra element of uncertainty to the economic outlook, and have led to a noticeable increase in Korea's stock market and exchange rate volatility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet